Identification of Ibuprofen, Ketoprofen and Diclofenac by Using Test Strip Based on Imobilized Spesific Reagent on Nata De Coco Membrane - Karisma Wulan Ningtyas; Zulfikar Zulfikar; Bambang Piluharto (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2015)
Identification of ibuprofen, ketoprofen and diclofenac can be done by using simple method, it is called test strips. Test strip is made by immobilized specific reagents with entrapment technical on membrane matrix, which the used membrane nata de coco. Immobilization reagents with entrapment techniques aimed to trap reagent molecules in the space between the supporting material.The success of this imobilization can be seen from membran changing color after additional reagent and there is no leeching after additional sample on membrane. The used reagent for this identification is methyl red for ibuprofen and ketorpofen, copper acetate for ibuprofen, potassium iodide for ketorofen and mandelin for diclofenac. From the testing result can be seen that potassium iodide is the most specific reagent compare with the other threee other reagents. By using tes strip arranged with the strip made by this imobilization, test srtrip can be used to differentiate the tree other standard samples. Keywords: entrapment, nata de coco membrane, reagent spesific, test strip.